On Approval of the Concept of Education of Youth in the Spirit of Military and Patriotism - Akbarov Anvar Tojimatovich; Khajiyev Muhiddin Musajanovich; Alijanov Bakhtiyor Khoshimovich (Zien Journals, 2022)
There was a talk about increasing and intensifying the effectiveness of work on educating young people in the spirit of military patriotism, and you were briefed on what changes have been made. The concept was discussed in order to increase respect for the Fatherland
Keywords: Enhancing and intensifying; work on educating; Republic of Uzbekistan